Association between Socioeconomic Status and Incidence of Community-Associated Clostridioides difficile Infection — United States, 2014–2015. (19th January 2021) - Skrobarcek, Kimberly A; Mu, Yi; Ahern, Jennifer; Basiliere, Elizabeth; Beldavs, Zintars G; Brousseau, Geoffrey; Dumyati, Ghinwa; Fridkin, Scott; Holzbauer, Stacy M; Johnston, Helen; Kainer, Marion A; Meek, James; et al.
Abstract: We evaluated the association between socioeconomic status (SES) and community-associated Clostridioides difficile infection (CA-CDI) incidence across 2474 census tracts in 10 states. Highly correlated community-level SES variables were transformed into distinct factors using factor analysis. We found low SES communities were associated with higher CA-CDI incidence.